Metal–organic framework derived nanozymes in biomedicine - Wang, Dongdong (2021)
Nanozymes that integrate the advantages of both nanomaterials and natural enzymes have accumulated enormous research interest over the past decades because of the opportunity it provides to appreciate and further cultivate artificial enzymes with comparable property. By mimicking the coordination environments of the catalytic sites in natural enzymes, nanozymes with confined nanostructures can serve as substitutes for many catalytic processes with comparable activity and robust stability even in harsh conditions. Since the pioneered report about peroxidase-mimicking ferromagnetic nanoparticles in 2007, the nanozymes are specialized for nanomaterials with intrinsic enzyme-mimicking property. With the rapid development in nanoscience and nanotechnology, nanomaterials with superior advantages such as large-scale production, desired activity, and robust stability can bridge the natural enzymes with nanozymes. Metal-organic frameworks (MOFs) and their derivatives hold a great promise to serve as direct surrogates of conventional enzymes for enzymatic reactions. According to the chemical nature, MOF-based nanozymes can be divided into three main categories: pristine MOFs, enzyme-encapsulated MOF composites, and MOF-based derivatives. Due to the versatility of metallic nodes and bridging linkers together with the feasibility of post-synthetic engineering and modification, MOFs and their derivatives are envisioned as one of the most appropriate surrogates for this purpose. Using MOFs as precursors or sacrificial templates, multiple MOF-based derivatives including carbon-based nanomaterials (e.g., heteroatom-doped carbon or carbon with M-N-C moiety), metal oxide/carbon nanoparticles, and metal/carbon nanomaterials can be rationally synthesized through one-step direct carbonization/oxidation or indirect post-treatments of MOFs (e.g., bridging linker-exchange and metallic node-doping). Compared with the existing nanozymes, MOF-based derivatives open up a new avenue for constructing mesoporous nanozymes. In this way, the intrinsic mesoporous property of MOFs can still be maintained, while the stability and activity can be largely improved. In this Account, we highlight some important research advances in MOF-based derivatives (including M-N-C moiety (M = single metal atom), metal oxide/carbon, metal/carbon, and MOF derivatives obtained through post-synthetic linker exchange and metal doping strategies) with enzyme-mimicking activity. We also portray that, through integrating physicochemical properties of mesoporous nanomaterials and enzymatic activities of natural enzymes, MOF-derived nanozymes can provide multifunctional platforms in biomedical community such as anti-bacteria, biosensor, imaging, cancer therapy, and environmental protection. Finally, we propose future design principles and possible research approaches for deeper understanding of mechanisms, thus pointing out future research directions to offer more opportunities for conventional enzyme-engineering industry.